Primary Burkittʼs Lymphoma of the Ovary in Early Weeks of Pregnancy – A Case Report - Steininger, H.; Gruden, J.; Müller, H. (Geburtshilfe und Frauenheilkunde, 2012)
Primary ovarian Burkittʼs lymphoma is a rare tumour predominantly affecting children and young adults. We report here on a 17-year-old pregnant woman with a Burkittʼs lymphoma of the left ovary. After tumour removal and induced abortion, the patient underwent polychemotherapy. Full remission was achieved 7 months after the initial diagnosis.
Keywords: adolescence; ovarian tumour; pregnancy